Role of Microglia in Ataxias. Issue 9 (19th April 2019) - Ferro, Austin; Sheeler, Carrie; Rosa, Juao-Guilherme; Cvetanovic, Marija
Abstract: Microglia, the resident macrophages of the central nervous system, critically influence neural function during development and in adulthood. Microglia are also profoundly sensitive to insults to the brain to which they respond with process of activation that includes spectrum of changes in morphology, function, and gene expression. Ataxias are a class of neurodegenerative diseases characterized by motor discoordination and predominant cerebellar involvement. In case of inherited forms of ataxia, mutant proteins are expressed throughout the brain and it is unclear why cerebellum is particularly vulnerable. Recent studies demonstrated that cerebellar microglia have a uniquely hyper-vigilant immune phenotype compared to microglia from other brain regions. These findings may indicate that microglia actively contribute to cerebellar vulnerability in ataxias. Here we review current knowledge about cerebellar microglia, their activation, and their role in the pathogenesis of ataxias. In addition, we briefly review advantages and disadvantages of several experimental approaches available to study microglia. Graphical Abstract: Unlabelled Image Highlights: Microglia, the resident macrophages of the central nervous system, critically influence neural function during development and in adulthood. The ataxias are a family of neurological disorders characterized by loss of balance and coordinated motor function and cerebellar neurodegeneration. Cerebellar microglia have a uniquely hyper-vigilant immune phenotype that may explain cerebellar vulnerability despite widespread expression of mutant proteins in inherited ataxias. Cerebellar microglia are present in early stages of many types of ataxias, and modulating microglial activation indicates that they may contribute to pathogenesis.